Maternal Transmission Ratio Distortion of GNAS Loss‐of‐Function Mutations. (13th January 2020) - Snanoudj, Sarah; Molin, Arnaud; Colson, Cindy; Coudray, Nadia; Paulien, Sylvie; Mittre, Hervé; Gérard, Marion; Schaefer, Elise; Goldenberg, Alice; Bacchetta, Justine; Odent, Sylvie; Naudion, Sophie; et al.
ABSTRACT: Pseudohypoparathyroidism type 1A (PHP1A) and pseudopseudohypoparathyroidism (PPHP) are two rare autosomal dominant disorders caused by loss‐of‐function mutations in the imprinted Guanine Nucleotide Binding Protein, Alpha Stimulating Activity ( GNAS ) gene, coding Gs α. PHP1A is caused by mutations in the maternal allele and results in Albright's hereditary osteodystrophy (AHO) and hormonal resistance, mainly to the parathormone (PTH), whereas PPHP, with AHO features and no hormonal resistance, is linked to mutations in the paternal allele. This study sought to investigate parental transmission of GNAS mutations. We conducted a retrospective study in a population of 204 families with 361 patients harboring GNAS mutations. To prevent ascertainment bias toward a higher proportion of affected children due to the way in which data were collected, we excluded from transmission analysis all probands in the ascertained sibships. After bias correction, the distribution ratio of the mutated alleles was calculated from the observed genotypes of the offspring of nuclear families and was compared to the expected ratio of 50% according to Mendelian inheritance (one‐sample Z ‐test). Sex ratio, phenotype of the transmitting parent, and transmission depending on the severity of the mutation were also analyzed. Transmission analysis was performed in 114 nuclear families and included 250 descendants. The fertility rates were similar between male and female patients. We showed an excess of transmission from mother to offspring of mutated alleles (59%, p = .022), which was greater when the mutations were severe (61.7%, p = .023). Similarly, an excess of transmission was found when the mother had a PHP1A phenotype (64.7%, p = .036). By contrast, a Mendelian distribution was observed when the mutations were paternally inherited. Higher numbers of females within the carriers, but not in noncarriers, were also observed. The mother‐specific transmission ratio distortion (TRD) and the sex‐ratio imbalance associated to PHP1A point to a role of Gs α in oocyte biology or embryogenesis, with implications for genetic counseling. © 2019 American Society for Bone and Mineral Research.